The effect of Future Expansion on Architectural Form of University Buildings Sulaimani University - the Old Campus as a Case Study - Ali, Alan Faraydoon; Salih, Chro A. Hama (Sulaimani Journal for Engineering Sciences, 2019)
Future expansion is an extension of an existing building by adding new parts or connecting with buildings in order to create new expression and function for the building, expansion in general deals with future situation, building as it doesn’t need expansions, but within time factor it needs the expansion and the changes. The expansion in educational buildings is very important and needed for the changes of the learning process , that’s why , the design of the educational buildings should be very re-actionable with the changes , beside reserving the formal unity of the new and old buildings and the needs of the learning process . This research ,study the relationship between Future Expansion on Architectural Form and the effect of Future Expansion on the architectural form of Kurdistan Region of Iraq university buildings, the problem of the research is lake of knowledge in studying the effects of expansion in the formal unity in university architecture, for that the study focused on two parts , the first is the theoretical side and the conceptual thoughts of the factors of the study , the second one is the practical study and the graphical analyzing of the case study(old campus of Sulaimani University), and discussing the outcomes ,and the conclusions of the study.
Keywords: Future Expansion; educational buildings; Sulaimani University